Caracterização das formigas epigeicas e arborícolas em fragmentos de cerrado do Sudeste Goiano - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
Part of the natural Brazilian cerrado is found in the form of small fragments, disturbed, isolated and, still, little studied. Intensive agriculture with soybean and corn contribute significantly to fragmentation and consequent degradation of the environment in the southeast region of Goiás. The evaluation of the degree of anthropization of certain environments has been carried out successfully, with the use of bioindicator insects of environmental quality, among them, the ants. The objective of this work is to characterize communities of epigeic and arboreal ants in cerrado fragments of the southeastern region of Goiás, bordered by soybean (main crop) and corn (second crop), in the dry and rainy seasons, and to correlate this community of ants with structural characteristics of the same forest fragment. The method of ants capture was performed with baited pitfall traps, distributed on the soil and on the tree. These traps, which operated for two consecutive hours, were distributed along transects, within of the forest fragment. For the different collection points (spatial disposition of the traps), specific fragments, collection season (dry and rainy) and stratification (whether collected in soil or in trees), richness and composition of the local ant community were estimated. A comparison of the communities of ants in different climatic conditions and local collection (frequency of capture of the morphospecies or guilds, represented as a group of morphospecies) was made by Jacknife Estimator 1, Similarity and Dissimilarity of Jaccard (UPGMA), Analysis of Simylarities (ANOSIM) and Cophenetic Correlation Analysis. Linear Regression was used to correlate the similarity of the ant communities and the distance from the edge of the cerrado fragments investigated. Also, in our study we verified some characteristics of the arboreal component (species richness, species density and basal area of tree trunk) and correlated them with ant richness. To investigate the relationship between these functional traits and ant richness, Principal Component Analysis (PCA) was used. The suggestion of indicator species of environmental quality was confirmed by Individual Value of Indication (IndVal). We identified 52 morphospecies of ants in five fragments of cerrados studied. No significant difference in ant richness was verified between the tree and soil strata. In the arboreal strata, the richness of ants was significantly higher in the rainy season. In relation to the epigeic ants, no significant difference was verified in the richness of ants between the dry and rainy periods. Analysis ANOSIM shows significant difference in the composition of the communities of ants in the different fragments of cerrado, in the arboreal strata and soil. The same situation was observed in the total community of arboreal and epigeic ants. However, the analysis adoted does not provide a clean view of specific guilds. Also, the UPGA analysis did not show a pattern of similarity in the composition of the community of arboreal and epigeic ants in relation to the point of capture (edge effect). This non significant linear relationship between the similarity of the ant communities and the distance between the edges of the fragments was also verified in our study. PCA analysis evidenced that points further inside the fragment presented higher values of richness of ant species and larger sizes of the trees (which we inferred from the basal area of the trunk). O IndVal suggested two indicator species of environmental quality for the stratum soil, Pheidole cf. radoszkowskii (Mayr, 1884) and Crematogaster cf. stollii (Forel, 1885) and, didn´t suggest significantly, no indicator species for the tree stratum. Considering that ants are mediators of different functional roles, changes in the structure of local communities will implicate changes in general ecosystem processes, make these insects important bioindicators of environmental quality.
Keywords: Formicidae; Guildas; Riqueza; Estratificação; Similaridade; Antropização; Formicidae; Guilds; Richness; Stratification; Similarity; Anthropization; CIENCIAS AGRARIAS